Answer:
t₁ = 3.33s, h = 9 H
Step-by-step explanation:
let the v₁ = initial velocity of the faster stone and v₂ = initial velocity of the slower stone
using equation of motion and displacement equals to zero since the stone returned to the point of projection
y - y₀ = v₁ t - 1/2gt²
- v₁ t = - 1/2gt²
2v₁ t / t² = g
g = 2v₁ / t
repeat the same produce for the slower stone where the time = t₁
y-y₀ = v₂t₁ - 1/2 gt₁²
- v₂t₁ = - 1/2 gt₁²
t₁ = 2v₂ / g = 2v₂ / (2v₁ / t) = (2v₂ / 2v₁) × t
and
v₁ = 3v₂
t₁ = (2v₂ / 2v₁) × t = (v₂ / 3v₂) × 10 = 3.33 s
b) using the equation of motion
vf₂² = v₂² - 2gH
since the body stop momentarily at maximum height
- v₂² = - 2gH
v₂² / 2H = g
repeating the same procedure for the faster stone
vf₁² = v₁² - 2gh
- v₁² = - 2gh
v₁²/ 2g = h
substitute for g
h = v₁² / 2(v₂² / 2H ) = (v₁² / v₂²) × H = (3v₂)² / (v₂² ) × H = 9H